The prognostic effect of cardiac rehabilitation in the era of acute revascularisation and statin therapy: A systematic review and meta-analysis of randomized and non-randomized studies – The Cardiac Rehabilitation Outcome Study (CROS). (December 2016) - Rauch, Bernhard; Davos, Constantinos H; Doherty, Patrick; Saure, Daniel; Metzendorf, Maria-Inti; Salzwedel, Annett; Völler, Heinz; Jensen, Katrin; Schmid, Jean-Paul; ,
Background: The prognostic effect of multi-component cardiac rehabilitation (CR) in the modern era of statins and acute revascularisation remains controversial. Focusing on actual clinical practice, the aim was to evaluate the effect of CR on total mortality and other clinical endpoints after an acute coronary event. Design: Structured review and meta-analysis. Methods: Randomised controlled trials (RCTs), retrospective controlled cohort studies (rCCSs) and prospective controlled cohort studies (pCCSs) evaluating patients after acute coronary syndrome (ACS), coronary artery bypass grafting (CABG) or mixed populations with coronary artery disease (CAD) were included, provided the index event was in 1995 or later. Results: Out of n  = 18, 534 abstracts, 25 studies were identified for final evaluation (RCT: n  = 1; pCCS: n  = 7; rCCS: n  = 17), including n  = 219, 702 patients (after ACS: n  = 46, 338; after CABG: n  = 14, 583; mixed populations: n  = 158, 781; mean follow-up: 40 months). Heterogeneity in design, biometrical assessment of results and potential confounders was evident. CCSs evaluating ACS patients showed a significantly reduced mortality for CR participants (pCCS: hazard ratio (HR) 0.37, 95% confidence interval (CI) 0.20–0.69; rCCS: HR 0.64, 95% CI 0.49–0.84; odds ratio 0.20, 95% CI 0.08–0.48), but the single RCT fulfilling Cardiac Rehabilitation Outcome Study (CROS) inclusion criteria showed neutral results. CR participation was also associated with reduced mortality after CABG (rCCS: HR 0.62, 95% CI 0.54–0.70) and in mixed CAD populations. Conclusions: CR participation after ACS and CABG is associated with reduced mortality even in the modern era of CAD treatment. However, the heterogeneity of study designs and CR programmes highlights the need for defining internationally accepted standards in CR delivery and scientific evaluation.